Apolipoproteins E and J interfere with amyloid‐beta uptake by primary human astrocytes and microglia in vitro. Issue 4 (20th January 2014) - Mulder, Sandra D.; Nielsen, Henrietta M.; Blankenstein, Marinus A.; Eikelenboom, Piet; Veerhuis, Robert
<x xml:space="preserve">Abstract</x> Defective clearance of the amyloid‐β peptide (Aβ) from the brain is considered a strong promoter in Alzheimer's disease (AD) pathogenesis. Astrocytes and microglia are important mediators of Aβ clearance and Aβ aggregation state and the presence of amyloid associated proteins (AAPs), such as Apolipoproteins E and J (ApoE and ApoJ), may influence Aβ clearance by these cells. Here we set out to investigate whether astrocytes and microglia differ in uptake efficiency of Aβ oligomers (Aβoligo) and Aβ fibrils (Aβfib), and whether the Aβ aggregation state and/or presence of AAPs affect Aβ uptake in these cells in vitro. Adult human primary microglia and astrocytes, isolated from short delay post‐mortem brain tissue, were exposed to either Aβoligo or Aβfib alone or combined with a panel of certain AAPs whereafter Aβ‐positive cells were quantified using flow cytometry. Upon exposure to Aβ combined with ApoE, ApoJ, α1‐antichymotrypsin (ACT) and a combination of serum amyloid P and complement C1q (SAP‐C1q), a clear reduction in astrocytic but not microglial Aβoligo uptake, was observed. In contrast, Aβfib uptake was strongly reduced in the presence of AAPs in microglia, but not in astrocytes. These data provide the first evidence of distinct roles of microglia and astrocytes in Aβ clearance. More importantly we show that Aβ clearance by glial cells is negatively affected by AAPs like ApoE and ApoJ. Thus, targeting the association of Aβ with AAPs, such as ApoE and ApoJ, could serve as a therapeutic strategy to increase Aβ clearance by glial cells. GLIA 2014;62:493–503